An Analysis of Data Collection Tools Used When Completing Functional Vision Assessments. (January 2021) - Kaiser, Justin T.; Herzberg, Tina S.
Introduction: This study analyzed 39 data collection tools used by teachers of students with visual impairments when completing functional vision assessments (FVAs). Methods: In 2017, teachers of students with visual impairments submitted data collection tools used in the FVA process. These tools were then compared with the 23 FVA components suggested by two established resources, Erin and Paul and D'Andrea and Farrenkopf. Results: The most commonly assessed skills and abilities were near visual acuity, distance visual acuity, and color perception. Only five of the submitted data collection tools contained at least 80% of the FVA components identified by the established resources. Fewer than 25% of the tools incorporated an orientation and mobility (O&M) screening. Discussion: There was considerable variation in the background information, medical data, and visual skills information that was collected. Variability in the data collected during the FVA process may impact a teacher's recommendations, including referrals for specialized evaluations such as O&M and clinical low vision evaluations. Implications for practitioners: Since FVA reports are used by Individualized Education Program teams, it is essential that data collection tools used during the assessment process are complete and address key areas such as near visual acuity and color perception. Teachers should carefully review their tools to determine whether the data collected are sufficient to make informed recommendations regarding accommodations, goals, and referrals. If the data collected are not sufficient, then the tools should be revised or additional data should be collected.